The Degree of Employment of the Habits of Mind by the Biology Teachers in Teaching in the Light of Gender and Experience Variables - Shihab, Abdalla (Dirasat: Educational Sciences, 2020)
The study aimed to investigate the degree of employing the habits of mind in teaching by biology teachers in light of the variables of gender and experience in Jordan. The study used the descriptive method to answer the study questions. A questionnaire was developed after verifying its validity and reliability. The questionnaire was applied to a sample of (120) male and female teachers chosen from public and private schools in Wadi Al-Seer district in the capital, Amman. The results showed that the degree of employing habits of mind in teaching by biology teachers was medium. The results also showed a statistically significant difference between the biology teachers' estimates of the habits of mind according to the gender variable in favor of female teachers. The study also showed that there are no statistically significant differences for the biology teachers' estimates according to the variable of years of experience and the interaction between gender and years of experience. The study recommended the necessity of employing the habits of mind in teaching by biology teachers.